Some leguminous trees providing useful fruits in the north of Brazil - Arkcoll, David B. (Pesquisa Agropecuaria Brasileira, 2014)
Several species of legume fruit trees are described briefly. Trees of Parkia platycephala Benth. (Faveira) produce as much as 200 kg of dry starchy pods which are fed to livestock in the dry part of the year in Piauí and the Tocantins region. Pentaclethra macroloba (Willd.) Kuntze (Pracachy) is a common tree along the banks of the rivers Negro and Amazon. The large pods contain seeds with 45% oil when dry that has been collected in the past and extracted for cooking, candle and soap production. Extracted meal is fed to livestock. Swartzia sp. (uabu) produce large seeds that form an important item of the diet of the toototóbi group (part of the Yanomamo tribe on the Brazil/Venezuela border) at certain times of the year. They are said to be toxic unless well cooked and soaked. Cassia leiandra Benth. (Marimari) is a common tree on the floodplain of the Amazon river. Its long pods contain flat seeds surrounded by a soft green edible pulp that is bitter sweet and pleasant enough to reach local markets. Hymenaea courbaril Linn. (West Indian locust, Stinking toe, Jatobá, Jutaí, Copal) and many other members of the same genus produce pods which contain an edible powdery pulp surrounding the seeds within. The tree is better known for its hardwood and hard resin used to produce a varnish. Dipteryx odorata (Aulb.) Willd. (Tonka bean, Cumaru) have seeds which are collected and extracted industrially to produce coumarin. This is used as a vanilla substitute, as a scent for tobacco and in perfumes. This species has a very hard wood and is being tested as a plantation crop by foresters in the Amazon. Two species of Inga, I. edulis Mart., and I. macrophyla H.B.K. are commonly grown in Amazon gardens for the sweet edible tests that surround the seeds in their large pods. Those collected from wild trees of I. cinnamomea Spruce ex Benth. are also sold in the market.